Drug radiotherapy combinations: Review of previous failures and reasons for future optimism. Issue 2 (February 2015) - Higgins, Geoff S.; O'Cathail, Sean M.; Muschel, Ruth J.; McKenna, W. Gillies
Highlights Combined chemo-radiotherapy typically improves clinical outcomes but increases side-effects. Trials with targeted radiosensitising and hypoxia modifying drugs have been disappointing. The reasons for this include a lack of biomarkers to identify those patients likely to benefit. New drug strategies to augment radiotherapy offer great cause for optimism.